english english - Syarifatul Ulya; Dea Ryangga; Wahyu Edy Wibowo; Nuruddin Nasution; Supriyanto Ardjo Pawiro (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Regarding the increasing use of small-field photons in clinical treatment, in this study, we investigate the use of small-field electron beams in clinical treatment. This study aimed to evaluate small-field electron beam dosimetry of the nasopharyngeal, thyroid, and ethmoid sinus carcinoma cases. Dose measurement was done using EBT3 film. In nasopharyngeal cases with a homogenous area and irregular surface, the dose discrepancies for 6 MeV energy were unpredictable except for the 5×5 cm2 field size. For all energies in 5×5 cm2 field size, the dose discrepancies were less than 3%. In these cases, we found that a smaller electron beam field will increase the percentage of the dose discrepancy. This is caused by the effect of the lateral scatter disequilibrium in a small field electron beam. For ethmoid sinus cases, dose discrepancy depends on the field size and inhomogeneity of bone and tissue organ. Based on the evaluation of doses on the spinal cord, chiasm, and larynx (OAR), it can be seen that these organs received a very small dose. From this result, a small field electron beam is recommended for cases with a homogeneous target. However, in cases with a heterogenous target, further investigation is needed.